Analisis Kemampuan Pemahaman Konsep Matematis pada Materi Segitiga dan Segiempat Ditinjau Berdasarkan Karakteristik Cara Berpikir - Bella Nurbaiti Purwandini; Aprilia Nurul Chasanah; Zuida Ratih Hendrastuti (ARITHMETIC: Academic Journal of Math, 2022)
The research was done for analyze understand mathematical concepts of students on the material of triangular and quadrangular in terms of the characteristics of the student's way of thinking. This type of research is descriptive qualitative. The subjects in this study were students of class VII F and VII G of SMP Negeri 3 Muntilan. Subject selection procedure using purposive sampling. Data collection techniques use tests of mathematical concept comprehension ability, questionnaires of characteristics of ways of thinking, interviews, and documentation. The results showed that (1) the characteristics of concrete sequential thinking with Ability to understand high-category mathematical concepts can meet all indicators of understanding mathematical concepts, in the medium category it can meet 5 indicators and the low category only meet 3 indicators; (2) characteristics of abstract sequential thinking with the ability to understand mathematical concepts in the high category can meet 6 indicators, in the medium category it can only meet 5 indicators, and in the low category only meet 4 indicators; (3) the characteristics of concrete random thinking with the ability to understand mathematical concepts in the high category can meet 6 indicators, in the medium category it can only meet 5 indicators, and in the low category it can only meet 3 indicators; (4) characteristics of abstract random thinking with high ability to understand mathematical concepts can meet 6 indicators, in the medium category it can only meet 4 indicators and in the low category only meet 3 indicators.